Functions of Emojis in Indonesian College Students' Online Communication on Social Media X - Dewi, Amanda Kusuma; Sukaton, Ounu Zakiy (Universitas Brawijaya, 2025)
With the advent of communication technology, emojis have become inseparable in online communication, acting as paralinguistic elements in written online communication. This study investigates how emojis contribute to online written communications and their prominent functions, specifically in Indonesian college students' communication observed from reply posts in the X automated base account,